INTERPRETASI HUKUM ISLAM TERHADAP LEGALITAS AMIL ZAKAT FITRAH DI SMA NU GENTENG KABUPATEN BANYUWANGI - Ansari; Halimakki (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
This research uses a field research approach with a qualitative typewhich is carried in high school NU Genteng Banyuwangi and have anpositive impact, Zakat Fitrah in Genteng Banyuwangi tile high schoolcannot be referred to as amyl, in syar’i charity of the committee in highschool NU tile roofs as the representative of the people who paid thecharity, because the creation of the charity paid muzakki in shape byteachers of religion.